Reduced microstructural white matter integrity is associated with the severity of physical symptoms in functional neurological disorder - Nicolas Gninenko; Eliane Müller; Selma Aybek (NeuroImage: Clinical)
Background: Functional neurological disorder (FND) is linked to functional changes in brain networks without an underlying brain lesion. However, the dichotomy between functional and structural changes has been challenged by research suggesting that not only functional but also anatomical alterations in the gray and white matter may underlie a subset of symptoms. This study aimed to characterize white matter microstructural integrity and its association with patient-reported and clinician-rated physical symptoms’ severity in a large sample of FND patients. Methods: Diffusion-weighted imaging data were collected from 85 FND patients with mixed symptoms and 75 healthy controls (HCs), together with illness duration, clinician-rated (S-FMDRS & CGI), and patient-reported (SF-36) symptom severity. Microstructural integrity was computed based on probabilistic tractography using the Desikan-Killiany parcellation. Results: Compared to HCs, patients with FND presented widespread reduced microstructural integrity stemming from regions such as the right lateral orbitofrontal cortex, insula, putamen, and superior temporal regions. After adjusting for depression and anxiety, these differences were no longer significant. Within-group analysis revealed that reduced microstructural integrity, particularly in the left precuneus and left superior parietal cortex, was strongly correlated with both patient-reported and clinician-evaluated severity of physical symptoms in FND patients. Conclusion: Patients with FND present widespread reduced microstructural integrity in the brain, predominantly originating from temporoparietal, paralimbic and associated regions involved in emotion regulation and body awareness. These changes seem to be partly explained by comorbid mood disorders and the severity of physical symptoms, suggesting a plasticity phenomenon rather than trait biomarkers, which warrants further investigation in longitudinal study designs.